Analysis of Water Quality Pollution Index Asahan river in Tanjungbalai City - Virna Br Sinulingga; Ternala Alexander Barus; Hesti Wahyuningsih (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
The Asahan River, located in the Tanjungbalai city area, is used for plantation, agriculture, animal husbandry activities, toilet washing facilities, hospitals, hotels, settlements, and industry causing the decrease water quality of Asahan River. The purpose of this study was to analyze the water quality and status of the Asahan River water quality in the Tanjungbalai City Area and develop a pollution control strategy that needs to be implemented to prevent a decrease in the Asahan River water quality in the Tanjungbalai City Area. Purposive sampling technique as used to determine the sampling station. In this study, there were 6 sampling stations based on the activities of the local community with 3 repetitions of sampling. The data analysis techniques from this study are Water Quality Analysis using the Pollution Index (IP) Method and Water Pollution Control Strategy Analysis. The results of water quality analysis based on the pollution index on Asahan river water in Tanjungbalai City show that the average water pollution index is in the moderately polluted category. The maximum of river water pollution index results were at station 2 is 9,086 and the minimum of river water pollution index results were at station 5 is 6,111.Water pollution occurs due to the parameters of phosphate, detergent, oil and grease, and total coliform which have exceeded the quality standard threshold based on Government Regulation of the Republic of Indonesia Number 21 of the year 2022 concerning Management of Water Quality and Control of Class I Water Pollution.Keywords:Asahan RiverWater pollution IndexWater Quality